Risk Assessment of Tuberculosis in Patients With Chronic Mental Illness and Related Factors: A Population‐Based Cohort Study in Taiwan - Li‐Chen Hung; Pei‐Tseng Kung; Tung‐Han Tsai; Wen‐Chen Tsai; Kuang‐Hua Huang (The Clinical Respiratory Journal, 2025)
ABSTRACT Introduction Tuberculosis (TB) is a globally prevalent chronic infectious disease. The World Health Organization estimates that mental illnesses will become the leading cause of global disease burden in 2030. The inability to detect and provide proper treatment for TB in mental illness patients is an epidemic prevention blind spot. The objective of this study was to retrospectively compare the incidence of TB between the general public and mental illness patients. Methods This study used data across Taiwan from 2002 to 2013. The National Health Insurance Research Database, Registry for Catastrophic Illness Patients, Tuberculosis Database, and Household Registration Records of Taiwan were analyzed. Propensity score matching was used to reduce basic characteristic differences between mental illness patients and the general public. The conditional Cox proportional hazards model and cumulative risk curve were used to compare their risk of developing TB. Results It was shown that TB incidence was 87 and 71 per 100 000 person‐years in mental illness patients and the general public, respectively. The risk of developing TB in mental illness patients was 1.48 times (95% CI: 1.38–1.59) that of the general public. Conclusion Mental illness patients are a high‐risk population for TB and should be listed as key subjects for TB prevention and control.